Penerapan Metode Scramble Dalam Maharoh Kitabah Siswa Kelas VII di MTs Ihsaniyah Balapulang Tegal - muflichatun, fiqi; Yahya, Slamet (AlFaqrah: Journal of Arabic Studies, 2026)
This study aims to describe the implementation of the scramble method in learning maharah kitabah (Arabic writing skills) of seventh-grade students at MTs Ihsaniyah Balapulang Tegal. Writing skills are considered one of the most challenging aspects of Arabic language learning because they require mastery of vocabulary, grammatical structure, and the ability to organize ideas logically. This research employed a descriptive qualitative approach to explore the learning process and student responses in a natural classroom setting. Data were collected through classroom observations, interviews with the Arabic language teacher and students, and documentation of learning materials and students’ written work. The findings show that the scramble method was implemented through several structured stages, including preparation of scrambled words or sentences, explanation of instructions, student activities in rearranging the language elements, and joint evaluation and reflection. The application of this method encouraged students to actively participate, think critically, and collaborate during the learning process. Students demonstrated increased motivation, confidence, and ability to construct Arabic sentences with more accurate structures. The learning atmosphere became more engaging and interactive compared to conventional teacher-centered instruction. In conclusion, the scramble method proved to be an effective and innovative instructional strategy for developing Arabic writing skills at the Madrasah Tsanawiyah level. This method can serve as an alternative approach to enhance students’ engagement and writing competence in Arabic language learning.